Development and Validation of a Multimedia Based-Module in Science for TVL Track - Sheila S Padua; Honelly Mae S Cascolan (ASEAN Journal of Basic and Higher Education, 2020)
This study aimed to develop and validate a multimedia-based module in teaching Physical Science among Senior High School students under the Technical-Vocational-Livelihood Track. This research made utilized the Rapid Application Development (RAD) in developing the module using the Microsoft Visual Studio with Visual Basic as the Programming Language and also used the Research and Development Design (R & D) in validating the said module. After the development phase of the multimedia-based module, Science and IT experts were asked to evaluate the developed module. Results showed that the Level of Validity of the developed Multimedia-Based Module is Highly Valid along its Content, Format, Presentation and Organization, Accuracy and Recency of Information. The Online Readability Index of the Multimedia Based Module is appropriate for Grade 11 learners.